Simulation of the catalytic hydrocarbons dehydrogenation reactor under reduced H2 pressure; Chemical Reactors (CHEMREACTOR-22) - Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Frantsina E. V. Evgeniya Vladimirovna; Kozlov I. A. Igor Anatoljevich; Platonov V. V.; Fefelova K. O. Kseniya Olegovna (2016, 2016)
Title screen